INTERPLAY OF INFLAMMATION AND METABOLIC FACTORS IN COMORBID OBESITY AND ARTERIAL HYPERTENSION OF HIGH AND VERY HIGH RISK - I. V. Kologrivova; O. A. Koshelskaya; T. E. Suslova; I. V. Vinnitskaya; E. S. Kravchenko; O. A. Trubacheva (Российский кардиологический журнал)
Aim. Evaluation of the FoxP3+ T-regulatory lymphocytes (Treg) content in overweight and obesity in arterial hypertension (AH) patients of high and very high risk, and relation of Treg amount with the parameters of lipid and carbohydrate metabolism.Material and methods. A momentary cross sectional study was done, that included 39 patients with AH of high and very high cardiovascular risk with anthropometric signs of overweight and grade 1 obesity. For identification of Treg, intracellular expression of FoxP3 transcriptional factor was assessed. In the blood serum, high sensitive C-reactive protein (hsCRP) was measured, with leptin, adiponectin, parameters of lipid and carbohydrate metabolism.Results. By the ROC-analysis, the content of FoxP3+ Treg below 3,18% makes it to identify patients with hsCRP >3 mg/L (sensitivity — 74%; specificity — 68%). Subgroups were selected that differ by the content of FoxP3+ of T-regulatory lymphocytes (subgroup 1: patients with the level of FoxP3+ Treg <3,18%; subgroup 2: patients with FoxP3+ Treg >3,18%). In subgroup 1 patients there was direct correlation revelaed of FoxP3+ Treg-lymphocytes content and HDL cholesterol (Rs=0,564; p=0,012). Females of subgroup 1 were characterized by higher waist circumference comparing to the females of subgroup 2 (p=0,025); in males, however, there were no differences in waist circumference. In subgroup 1 male patients were characterized by lower HDL cholesterol comparing to women (p=0,005), however such difference was absent in the subgroup of patients with FoxP3+ Treg >3,18%. Among the patients of subgroup 2 the content of FoxP3+ Treg in males showed tendency to higher values comparing with females.Conclusion. In AH patients of high and very high risk, overweight and obesity grade 1, first time an association revealed of Treg lymphocytes and HDL concentration, that is related to higher rate of subclinical inflammation. Gender specifics is found for potential mechanisms of increase of FoxP3+ Treg-lymphocytes. The relations that revealed in our study underscore an opportunity to develop novel approaches to cardiometabolic risk stratification.